(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The rural economy is a component part of the concept of local economy, at the present moment the need for sustainable development starts from the creation of the seeds of degrowth for the local economy, as a generator of well-being. The synergy created locally through the European funds introduced in the local, rural economy determines a synergistic effect. The rural economy, as a component of the local economy, develops through the institutional factor and the human factor. The study wants to show methods for evaluating rural development in Romania, in the context of joining the European Union. The methodologies used are analysis and synthesis and they are usefull for private and public sector in helping them find new ways to improve rural life with European funds.